Leather pattern embossing roller and processing technology thereof

By laser cladding anti-corrosion and wear-resistant metal powder coating on the surface of the embossing roller, the shortening of service life caused by wear and corrosion of the embossing roller is solved, and higher wear and corrosion resistance is achieved.

CN119571311AActive Publication Date: 2025-03-07CHANGZHOU WUJIN GUANGYU EMBOSSING ROLLER MACHINERY

Patent Information

Application Number
CN202411746205.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing embossing rollers are prone to shorten their service life due to external wear and chemical corrosion after long-term use.

Method used

The laser cladding anti-corrosion and wear-resistant metal powder coating is used to pre-heat and use laser cladding anti-corrosion and wear-resistant metal powder coating after polishing, cleaning, coating resin, laser ablation, and acid etching treatment on the steel roller surface.

Benefits of technology

It significantly improves the surface wear and corrosion resistance of the embossing roller and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005163790600000131
    Figure BDA0005163790600000131
Patent Text Reader

Abstract

The invention discloses a dermatoglyph knurling roller and a processing technology thereof, and relates to the technical field of knurling rollers, in order to improve the wear resistance and corrosion resistance of the surface of the knurling roller, on the basis of a steel roller, the surface of the steel roller is coated with an anti-corrosion and wear-resistant metal powder coating through laser cladding, and a nano graphene material with a self-lubricating property is added into the steel roller, so that the anti-corrosion and wear-resistant metal powder coating is formed. After titanium dioxide is loaded on the surface of a nano graphene material and reduced, nano titanium metal particles are loaded on the surface of nano graphene, so that the bonding strength between the nano graphene and alloy powder after laser melting is improved, and the stripping phenomenon of a coating in the subsequent pressing process is avoided; therefore, on the basis of ensuring the overall strength of the steel roller, the wear resistance and corrosion resistance of the surface of the steel roller are improved, and the service life of the coating is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of embossing rollers, in particular to a leather grain embossing roller and a processing technology thereof. Background Art

[0002] Embossing rollers are suitable for pressing patterns on the surfaces of products such as plastics, metals, leather and even glass and ceramics, thereby improving the surface aesthetics and feel of the products. During the pressing process of the embossing roller, the processed products will be deformed on the surface under the action of external force to retain the embossed patterns. During this process, the surface of the embossing roller will be subjected to greater external force, which will often cause greater wear on its surface after long-term use. In addition, due to different processing materials, such as the pressing of products such as artificial leather, the chemical substances in them will often cause corrosion to the surface of the embossing roller, thereby aggravating the wear of the roller surface and seriously affecting its service life. Summary of the invention

[0003] The purpose of the present invention is to provide a leather grain embossing roller and a processing technology thereof to solve the problems raised in the prior art.

[0004] To achieve the above object, the present invention provides the following technical solution: a processing technology of a leather grain embossing roller, comprising the following steps:

[0005] S1. Preparation of leather grain embossing roller;

[0006] The surface of the steel roller blank is polished with sandpaper. After polishing, the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried. The resin coating in a predetermined area is ablated with a laser. After ablation patterns are formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid, heated to 45-60°C, and after immersion and acid etching for 5-25 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent. After the surface is cleaned with anhydrous ethanol and acetone again for 2-5 times, a leather grain embossing roller blank is obtained;

[0007] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0008] S21. The nanographene material is dispersed in deionized water, and after ultrasonic vibration dispersion for 1-2 hours, 20-80% of the volume of deionized water KH-550 silane coupling agent is added thereto, and the mixture is mixed for 3-5 minutes, and then ammonia water is added dropwise to adjust the pH value to 10-11, and the mixture is heated to 55-65°C, and ion irradiated for 2-4 hours, and then 3-5 times the volume of deionized water is added with anhydrous ethanol, and the mixture is centrifuged and filtered, and the precipitate is washed with anhydrous ethanol for 2-3 times to obtain amino-modified graphene;

[0009] S22. The amino-modified graphene is dispersed in anhydrous ethanol, ultrasonically dispersed for 1-2 hours, glacial acetic acid is added, the pH value is adjusted to 4-5, tetrabutyl titanate and deionized water are added thereto, stirred for reaction for 2-4 hours, centrifuged for precipitation, and vacuum dried to constant weight. The obtained product is placed in a hydrogen and argon atmosphere, heated to 600-650°C, and reduced at high temperature for 15-30 minutes, and then filled with nitrogen for cooling to obtain modified nanographene;

[0010] S23. Iron, chromium, nickel, cobalt and titanium are placed in a ball mill, ground to a desired particle size and then mixed, heated to 2100-2300°C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, mixed with modified nano-graphene, and vibrated and blended for 5-15 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0011] S3. Preheat the leather grain embossing roller blank to 300-350°C, and laser-clad the surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5-10g / min, the laser cladding power is 2.5-3kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0012] Furthermore, in step S1, after being polished with sandpaper, the surface roughness of the steel roller blank is 0.1-0.5 μm.

[0013] Furthermore, in step S1, the ablation pattern is dermatoglyphics.

[0014] Furthermore, in step S21, the mass ratio of the nanographene, deionized water and kH-550 type silane coupling agent is (0.05-0.1):1:(0.2-0.8).

[0015] Furthermore, in step S21, during the ion irradiation reaction, the ion beam energy is 5-10 KeV, and the ion beam current density is 2-4 μA / cm 2 .

[0016] Furthermore, in step S22, the mass ratio of the amino-modified graphene to tetrabutyl titanate and deionized water is 5:(2-10):(30-50).

[0017] Furthermore, in step S22, in the hydrogen and argon atmosphere, the volume ratio of hydrogen to argon is (1-3):(7-9).

[0018] Furthermore, in step S23, the alloy powder is composed of 45-55 parts of iron, 15-20 parts of chromium, 5-10 parts of nickel, 3-5 parts of cobalt, and 10-20 parts of titanium, by weight.

[0019] Furthermore, in step S23, the mass ratio of the alloy powder to the modified nano-graphene is 10:(0.3-0.8).

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] In order to improve the surface wear resistance and corrosion resistance of the embossing roller, the present invention laser-clads the surface of the steel roller with anti-corrosion and wear-resistant metal powder coating, thereby improving the surface wear resistance and corrosion resistance of the steel roller while ensuring the overall strength of the steel roller;

[0022] The invention first uses nanographene material as a raw material, disperses it in a KH-550 silane coupling agent, increases the number of amino groups on its surface under ion irradiation, and then improves the surface activity of the nanographene, and then places it in tetrabutyl titanate, utilizes the hydrolysis property of tetrabutyl titanate in water, deposits nano titanium dioxide on the surface of the nanographene, and then transfers the nanographene as a whole to a reducing atmosphere of hydrogen, and at a high temperature of more than 600°C, hydrogen reduces the titanium dioxide on the surface of the nanographene into nano-scale titanium metal particles;

[0023] On this basis, the present invention uses iron, chromium, nickel, cobalt and titanium as raw materials, melts them and granulates them to obtain alloy powder with a particle size of 30-50 microns. The iron element accounts for the largest proportion in the alloy powder, which can be effectively combined with the steel roller during laser cladding, thereby ensuring that the formed coating has sufficient bonding strength with the steel roller and avoiding the peeling of the coating during the subsequent pressing process. The addition of chromium, nickel and cobalt elements can ensure the corrosion resistance of the coating formed by the alloy powder after cladding; at the same time, the present invention also adds titanium element components to the alloy powder, thereby ensuring that during subsequent laser cladding, the nano-titanium metal particles on the surface of the modified nano-graphene can be combined with the alloy powder, thereby improving the bonding strength of the wear-resistant coating formed by the nano-graphene and the alloy powder; and in this process, since the nano-graphene material has excellent self-lubricating properties, the friction of the coating can be effectively reduced, and the service life of the coating can be effectively increased. DETAILED DESCRIPTION

[0024] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0025] The components of the steel roll blanks used in the examples and comparative examples of this application are as follows:

[0026] 0.042-0.045% C, 2.14-2.22% Cr, 0.21-0.36% Si, 0.52-0.6% Mn, 0.51-0.64% Ni, 1.05-1.14% Mo, 0.05-0.1% Nb, <0.025% S, <0.030% P, balance Fe;

[0027] The nanographene material used in this application has a sheet diameter of 5-10 microns and a thickness of 3-10 nm;

[0028] Embodiment 1. A processing technology of a leather grain embossing roller comprises the following steps:

[0029] S1. Preparation of leather grain embossing roller;

[0030] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0031] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0032] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 5KeV, and the ion beam current density to 2μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0033] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 2 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and separate the precipitate, vacuum dry to constant weight, place the resulting product in a mixed gas atmosphere of hydrogen and argon with a volume ratio of 2:8, heat to 600 ° C, high temperature reduction for 15 minutes, and then charge with nitrogen to cool to obtain modified nanographene;

[0034] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.3, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0035] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0036] Embodiment 2. A processing technology of a leather grain embossing roller comprises the following steps:

[0037] Compared with Example 1, this embodiment increases the ion beam energy and density in step S21;

[0038] S1. Preparation of leather grain embossing roller;

[0039] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0040] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0041] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 10KeV, and the ion beam current density to 4μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0042] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 2 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and separate the precipitate, vacuum dry to constant weight, place the resulting product in a mixed gas atmosphere of hydrogen and argon with a volume ratio of 2:8, heat to 600 ° C, high temperature reduction for 15 minutes, and then charge with nitrogen to cool to obtain modified nanographene;

[0043] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.3, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0044] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0045] Embodiment 3. A processing technology of a leather grain embossing roller, comprising the following steps:

[0046] Compared with Example 1, this example increases the amount of tetrabutyl titanate added in step S22;

[0047] S1. Preparation of leather grain embossing roller;

[0048] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0049] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0050] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 5KeV, and the ion beam current density to 2μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0051] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 10 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and separate the precipitate, vacuum dry to constant weight, place the resulting product in a mixed gas atmosphere with a volume ratio of hydrogen to argon of 2:8, heat to 600 ° C, high temperature reduction for 15 minutes, and then charge with nitrogen to cool to obtain modified nanographene;

[0052] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.3, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0053] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0054] Embodiment 4. A processing technology of a leather grain embossing roller, comprising the following steps:

[0055] Compared with Example 1, this embodiment increases the amount of modified nano-graphene added in step S23;

[0056] S1. Preparation of leather grain embossing roller;

[0057] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0058] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0059] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 5KeV, and the ion beam current density to 2μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0060] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 2 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and separate the precipitate, vacuum dry to constant weight, place the resulting product in a mixed gas atmosphere of hydrogen and argon with a volume ratio of 2:8, heat to 600 ° C, high temperature reduction for 15 minutes, and then charge with nitrogen to cool to obtain modified nanographene;

[0061] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.8, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0062] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0063] Embodiment 5. A processing technology of a leather grain embossing roller, comprising the following steps:

[0064] Compared with Example 1, this embodiment increases the powder feeding amount during laser cladding in step S3;

[0065] S1. Preparation of leather grain embossing roller;

[0066] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0067] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0068] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 5KeV, and the ion beam current density to 2μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0069] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 2 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and separate the precipitate, vacuum dry to constant weight, place the resulting product in a mixed gas atmosphere of hydrogen and argon with a volume ratio of 2:8, heat to 600 ° C, high temperature reduction for 15 minutes, and then charge with nitrogen to cool to obtain modified nanographene;

[0070] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.3, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0071] S3. Preheat the leather grain embossing roller blank to 300°C, and laser-clad the surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 10g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0072] Comparative Example 1. A processing technology for a leather grain embossing roller, comprising the following steps:

[0073] Compared with Example 1, this comparative example does not prepare the added modified nanographene;

[0074] S1. Preparation of leather grain embossing roller;

[0075] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0076] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0077] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size, mixed, heated to 2100 ° C, melted, spray granulated, cooled, and sieved to obtain a corrosion-resistant and wear-resistant metal powder coating with a particle size of 30-50 μm;

[0078] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0079] Comparative Example 2. A processing technology for a leather grain embossing roller, comprising the following steps:

[0080] Compared with Example 1, hydrogen reduction was not used in step S22 of this comparative example;

[0081] S1. Preparation of leather grain embossing roller;

[0082] The surface of the steel roller blank is polished with sandpaper until the surface roughness is 0.1-0.5 μm, and then the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried, and then the resin coating in a predetermined area is ablated with a laser, and after a skin-like pattern is formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid with a concentration of 30 wt%, heated to 45° C., and after acid etching for 10 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent, and the surface is cleaned again with anhydrous ethanol and acetone for 3 times to obtain a skin-like embossing roller blank;

[0083] S2. Preparation of anti-corrosion and wear-resistant metal powder coating;

[0084] S21. Disperse 5 parts of nanographene material into 100 parts of deionized water by weight, disperse under ultrasonic vibration for 1 hour, add 20 parts of KH-550 silane coupling agent, continue mixing for 3 minutes, add ammonia water to adjust the pH value to 10.5, heat to 60°C, set the ion beam energy to 5KeV, and the ion beam current density to 2μA / cm 2 , ion irradiation reaction for 2h, adding anhydrous ethanol 3 times the volume of deionized water to mix, centrifugal filtration, and continue to use anhydrous ethanol to wash the precipitate 2-3 times to obtain amino-modified graphene;

[0085] S22. Disperse 5 parts of amino-modified graphene in anhydrous ethanol by weight, ultrasonically disperse for 1 hour, add glacial acetic acid, adjust the pH value to 4.5, add 2 parts of tetrabutyl titanate and 30 parts of deionized water, stir and react for 2 hours, centrifuge and precipitate, and vacuum dry to constant weight to obtain modified nanographene;

[0086] S23. By weight, 51.5 parts of iron, 17.3 parts of chromium, 8.4 parts of nickel, 4.1 parts of cobalt, and 17.2 parts of titanium were placed in a ball mill, ground to the desired particle size and mixed, heated to 2100 ° C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, and mixed with modified nano-graphene in a mass ratio of 10:0.3, and vibrated and blended for 5 minutes to obtain an anti-corrosion and wear-resistant metal powder coating;

[0087] S3. Preheat the leather grain embossing roller blank to 300°C, and laser clad its surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5g / min, the laser cladding power is 2.5kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

[0088] Detection:

[0089] Take the steel material of the same material as the leather grain embossing roll blank as the blank, and prepare the anti-corrosion and wear-resistant metal powder coating according to the method of Example 1-5 and Comparative Example 1-2 respectively, and then clad it as the test sample;

[0090] The wear resistance of the test samples prepared in Examples 1-5 and Comparative Examples 1-2 was tested using a UMT-3 friction and wear tester. During the test, a 4mm GCr15 ball was used to apply a normal load of 5N to the sample, and the dry friction sliding was performed for 20 minutes at a rotation speed of 300rpm.

[0091] The hardness of the test samples prepared in Examples 1-5 and Comparative Examples 1-2 was tested using a Vickers microhardness tester;

[0092] According to GB / T 17897-1999, pitting weight loss test was performed on the test samples prepared in Examples 1-5 and Comparative Examples 1-2;

[0093] The test results are shown in the table below;

[0094]

[0095] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A processing technology for a leather grain embossing roller, characterized in that: The following steps are involved: S1. Preparation of leather grain embossing roller; The surface of the steel roller blank is polished with sandpaper. After polishing, the surface is cleaned with anhydrous ethanol and deionized water, dried, and a resin coating is applied to the surface and dried. The resin coating in a predetermined area is ablated with a laser. After ablation patterns are formed on the surface of the embossing roller blank, the whole body is immersed in nitric acid, heated to 45-60°C, and after immersion and acid etching for 5-25 minutes, it is taken out, and the remaining coating on the surface is removed with a cleaning agent. After the surface is cleaned with anhydrous ethanol and acetone again for 2-5 times, a leather grain embossing roller blank is obtained; S2. Preparation of anti-corrosion and wear-resistant metal powder coating; S21. The nanographene material is dispersed in deionized water, and after ultrasonic vibration dispersion for 1-2 hours, KH-550 silane coupling agent is added thereto, and the mixture is mixed for 3-5 minutes, and then ammonia water is added dropwise to adjust the pH value to 10-11, and the mixture is heated to 55-65° C., and then ion irradiated for 2-4 hours, and anhydrous ethanol with a volume of 3-5 times that of deionized water is added and mixed, and then centrifuged and filtered, and the precipitate is washed with anhydrous ethanol for 2-3 times to obtain amino-modified graphene; S22. The amino-modified graphene is dispersed in anhydrous ethanol, ultrasonically dispersed for 1-2 hours, glacial acetic acid is added, the pH value is adjusted to 4-5, tetrabutyl titanate and deionized water are added thereto, stirred for reaction for 2-4 hours, centrifuged for precipitation, and vacuum dried to constant weight. The obtained product is placed in a hydrogen and argon atmosphere, heated to 600-650°C, and reduced at high temperature for 15-30 minutes, and then filled with nitrogen for cooling to obtain modified nanographene; S23. Iron, chromium, nickel, cobalt and titanium are placed in a ball mill, ground to a desired particle size and then mixed, heated to 2100-2300°C for melting, spray granulated, cooled and sieved to obtain an alloy powder with a particle size of 30-50 μm, mixed with modified nano-graphene, and vibrated and blended for 5-15 minutes to obtain an anti-corrosion and wear-resistant metal powder coating; S3. Preheat the leather grain embossing roller blank to 300-350°C, and laser-clad the surface with anti-corrosion and wear-resistant metal powder coating. The powder feeding amount during laser cladding is 5-10g / min, the laser cladding power is 2.5-3kw, and the laser scanning speed is 3-8mm / s. After the laser cladding is completed, a leather grain embossing roller is obtained.

2. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S1, after being polished with sandpaper, the surface roughness of the steel roller blank is 0.1-0.5 μm.

3. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S1, the ablation pattern is dermatoglyphics.

4. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S21, the mass ratio of the nano-graphene, deionized water and kH-550 silane coupling agent is (0.05-0.1):1:(0.2-0.8).

5. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S21, during the ion irradiation reaction, the ion beam energy is 5-10 KeV, and the ion beam current density is 2-4 μA / cm 2 .

6. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S22, the mass ratio of the amino-modified graphene to tetrabutyl titanate and deionized water is 5:(2-10):(30-50).

7. The processing technology of a leather grain embossing roller according to claim 1 is characterized in that: In step S22, in the hydrogen and argon atmosphere, the volume ratio of hydrogen to argon is (1-3): (7-9).

8. The processing technology of a leather grain embossing roller according to claim 1, characterized in that: In step S23, the alloy powder is composed of 45-55 parts of iron, 15-20 parts of chromium, 5-10 parts of nickel, 3-5 parts of cobalt, and 10-20 parts of titanium, by weight.

9. The processing technology of a leather grain embossing roller according to claim 1, characterized in that: In step S23, the mass ratio of the alloy powder to the modified nano-graphene is 10:(0.3-0.8).

10. A leather grain embossing roller prepared by the processing technology described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nickel-based graphene oxide composite material with hollow cubic structure, preparation method of nickel-based graphene oxide composite material and graphene composite material for laser cladding

    CN116623163A

  • Inlays for security documents

    US20090315320A1

  • Methods of forming and methods of repairing earth-boring tools

    WO2017024322A2

Cited By

  • Metal plate for decorative plate release film and manufacturing process of metal plate

    CN121245248A